Comparing the diagnosis of gestational diabetes using the oral glucose tolerance test and a designed breakfast in a randomised, cross-over trial - Marais, Colin (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2022.